PENGARUH VALUE ADDED STATEMENT, ROA, ROE, DAN OPERATING CASH FLOW TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERGABUNG DI BEI - Beny, Beny; Sri Mendari, Anastasia (Widya Warta, 2011)
This study analyzed the influence of value added statement, return on asset, return on equity, and operating cash flow to the return of public companies listed on Indonesia Stock Exchange. This study was also intended to know which performance measures between value added concept and conventional accountany had the most significant effect to stakeholder’s return. To get the sample, this research made use of purposive sampling. The number of sample obtained was 19 companies. The data were analyzed using simple regression and SPSS program version 17. The result of the data analysis showed that ROA, ROE, and operating cash flow had influence on stakeholder’s return, whereas value added statement did not have influence on stakeholder’s return.